2023
DOI: 10.3390/ijms241713039
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Methamphetamine Administration Results in Axon Loss Prior to Somatic Loss of Substantia Nigra Pars Compacta and Locus Coeruleus Neurons in Male but Not Female Mice

Alexander Pilski,
Steven M. Graves

Abstract: Methamphetamine (meth) is a neurotoxic psychostimulant that increases monoamine oxidase (MAO)-dependent mitochondrial oxidant stress in axonal but not somatic compartments of substantia nigra pars compacta (SNc) and locus coeruleus (LC) neurons. Chronic meth administration results in the degeneration of SNc and LC neurons in male mice, and MAO inhibition is neuroprotective, suggesting that the deleterious effects of chronic meth begin in axons before advancing to the soma of SNc and LC neurons. To test this hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 103 publications
0
5
0
Order By: Relevance
“…4 Prolonged methamphetamine abuse is associated with neuronal loss in various brain regions, including the substantia nigra pars compacta and locus coeruleus, resulting in the deterioration of different cognitive domains, including memory and decision-making. [5][6][7] Kami et al reported that repetitive METH treatment impairs working memory through suppression of the ERK1/2 pathway in the hippocampus. 8 Furthermore, the cognitive decline induced by METH may be associated with the activation of inflammatory responses and the upregulation of pro-inflammatory cytokines in the hippocampus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Prolonged methamphetamine abuse is associated with neuronal loss in various brain regions, including the substantia nigra pars compacta and locus coeruleus, resulting in the deterioration of different cognitive domains, including memory and decision-making. [5][6][7] Kami et al reported that repetitive METH treatment impairs working memory through suppression of the ERK1/2 pathway in the hippocampus. 8 Furthermore, the cognitive decline induced by METH may be associated with the activation of inflammatory responses and the upregulation of pro-inflammatory cytokines in the hippocampus.…”
Section: Introductionmentioning
confidence: 99%
“…METH disrupts the normal neuronal activity in the brain by enhancing the release of neurotransmitters such as dopamine, serotonin, and glutamate 4 . Prolonged methamphetamine abuse is associated with neuronal loss in various brain regions, including the substantia nigra pars compacta and locus coeruleus, resulting in the deterioration of different cognitive domains, including memory and decision‐making 5–7 . Kami et al.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the loss of NE axons arising from the LC was detected as early as day 14 following the administration of 5 mg/kg METH. Both nuclei were affected concerning a decrease in neuron numbers, only following a double cumulative dose of METH (28 days of METH at 5 mg/kg) [ 28 ]. In this study, a stereological approach was used and the effects on axonal integrity were assessed by stereology of axonal length.…”
Section: Discussionmentioning
confidence: 99%
“…Again, since repeated administration of high doses of METH may produce nigrostriatal toxicity, it is important to analyze whether the occurrence of sensitized blood pressure in response to METH is concomitant either to damage to the DA nigrostriatal system or an alteration of the mesolimbic DA system. Again, since METH activity profoundly modifies norepinephrine (NE)-containing neurons in the pontine nucleus locus coeruleus (LC) [ 28 ], which is deeply involved in blood pressure adaptive changes [ 29 ], a morphological analysis was extended to LC. In addition, immunohistochemistry for the immediate early gene c-fos was carried out to roughly assess whether activation of these areas was produced, including the rostral ventrolateral medulla RVLM, which overlaps with the A1/C1 area.…”
Section: Introductionmentioning
confidence: 99%
“…Alexander Pilski and Steven M. Graves [34] focused on the effects of repeated methamphetamine (meth) administration on substantia nigra pars compacta (SN) and locus coeruleus (LC) neurons in a mouse model. They observed that repeated meth exposure produced SN and LC axonal deficits prior to somatic loss in males, consistent with a dying-back pattern of degeneration, whereas female mice were resistant to chronic methinduced degeneration.…”
mentioning
confidence: 99%